A Comprehensive Survey on Methods and Techniques for Automated Fruit Plucking - Shankarpure, Madhura Rajesh; Patil, Dipti Durgesh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In comparison of various product types in the farming, fruit farming has been more challenging than grain farming due to the challenges in its cultivation, harvesting in unstructured environment, high cost of safety during storage and timely distribution due to their short life. Fruit plucking becomes an important part due to its direct relation with the safety of potential return on farmer’s investment. After humans started farming, there is step by step changes in fruit plucking techniques. Regardless, this process still remains labor intensive and manual in nature. The population on world is growing at rapid pace and so is the world-wide demand of agricultural products. However, labor shortages have remained a limiting factor in agriculture production. To cope up with the upcoming growth as well as to reduce the wastage of perishable items like fruits, it’s important that the agriculture sector brings further automation. Sector needs to tackle the common fruit picking challenges through novel system solutions and improve the current systems. This paper shows the changes and growth in plucking techniques from ancient times to modern day plucking. Paper reviews the manual plucking techniques that involves the intensive risk and crude equipment with manual labors, to modern fruit plucking techniques based on computer vision and robotic systems. From this review, this paper intends to identify major research opportunities that are drafted under future research directions section.